2004
DOI: 10.1080/10937400490498084
|View full text |Cite
|
Sign up to set email alerts
|

Review of Studies Concerning the Tumorigenicity of 2-Butoxyethanol in B6c3f1 Mice and Its Relevance for Human Risk Assessment

Abstract: The U.S. National Toxicology Program (NTP) has completed 2-yr inhalation exposures in rats and mice with 2-butoxyethanol (BE). This review concerns the most significant findings from those studies and describes recent research into the mechanistic aspects of BE-mediated tumorigenesis in the mouse and the relevance of such effects to humans. Two tumor types were increased in B6C3F1 mice leading to the classification of "some evidence" of carcinogenicity: liver hemangiosarcomas in male mice and forestomach tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…TCEP has been classified as a category 2 reproductive toxicant and category 2 carcinogen (EU 2009). Another area of concern is the effect of the alcohols released as a result of hydrolysis of some of these OPEs, as it has been confirmed that butoxyethanol produced by the hydrolysis of tributoxy ethyl phosphate (TBEP), is not just a mutagen but also an endocrine disruptor (Boatman et al 2004). Overall, the ecotoxic effects of several chemical plastic additives including flame retardants and plasticizers are welldocumented in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…TCEP has been classified as a category 2 reproductive toxicant and category 2 carcinogen (EU 2009). Another area of concern is the effect of the alcohols released as a result of hydrolysis of some of these OPEs, as it has been confirmed that butoxyethanol produced by the hydrolysis of tributoxy ethyl phosphate (TBEP), is not just a mutagen but also an endocrine disruptor (Boatman et al 2004). Overall, the ecotoxic effects of several chemical plastic additives including flame retardants and plasticizers are welldocumented in the literature.…”
Section: Introductionmentioning
confidence: 99%